2018
DOI: 10.1111/jgh.14315
|View full text |Cite
|
Sign up to set email alerts
|

Amide proton transfer imaging to predict tumor response to neoadjuvant chemotherapy in locally advanced rectal cancer

Abstract: Pretherapeutic APT imaging can predict the tumor response to NAC in patients with LARC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
1
28
1
Order By: Relevance
“…DCE-MRI of rectal cancer demonstrated that tumors with better perfusion showed greater nodal and tumor downstaging after radiotherapy than poorly perfused tumors (38). However, our result on APT changes after NCRT contrasted with that of Nishie et al, who found that pretherapeutic mean APTw SI of low-response group was significantly higher than that of the high-response group (29). This difference may be explained by the fact that Nieshi et al used a different TRG grading criteria, which is according to necrosis or cytological changes of the tumor.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…DCE-MRI of rectal cancer demonstrated that tumors with better perfusion showed greater nodal and tumor downstaging after radiotherapy than poorly perfused tumors (38). However, our result on APT changes after NCRT contrasted with that of Nishie et al, who found that pretherapeutic mean APTw SI of low-response group was significantly higher than that of the high-response group (29). This difference may be explained by the fact that Nieshi et al used a different TRG grading criteria, which is according to necrosis or cytological changes of the tumor.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have reported that APTw imaging helps differentiate between pseudo-progression, radiation necrosis, and tumor recurrence in gliomas ( 25 )—it is superior to conventional MRI contrasts as well as to advanced functional imaging methods such as perfusion (dynamic susceptibility contrast and dynamic-contrast-enhanced) and spectroscopy ( 24 , 26 28 ). However, only one study assessed APTw MRI in evaluating the effect of chemoradiotherapy in LARC ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…APT imaging is not limited to central nervous system tumors or ischemic lesions (13)(14)(15)(16); more recently, it has been gradually developed and applied to the diagnosis of various system diseases (17)(18)(19)(20), but its application in aMCI is still in its infancy. The limbic system is a set of brain structures involved in emotion, learning, and memory, which are central to cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, mucin‐containing tumors—known to be unresponsive to chemotherapy—have been successfully stratified by APT MRI, as they yield higher APT signal intensities. The technique also predicted tumor response to neoadjuvant chemotherapy in locally advanced rectal cancer 6 …”
mentioning
confidence: 99%
“…The technique also predicted tumor response to neoadjuvant chemotherapy in locally advanced rectal cancer. 6 The ability to correlate quantitative imaging parameters with histopathology or oncogenic protein markers, such as the tumor protein p53 and Ki-67 index, would play a critical role in the assessment of prognostic factors for rectal adenocarcinoma, and it is an almost unexplored field.…”
mentioning
confidence: 99%